Financial Efficacy dan Financial Satisfaction: Ditinjau dari Perbedaan Gender - Peter Garlans Sina (Jurnal Manajemen Maranatha, 2013)
The purpose of this research was to examine the gender difference in financial efficacy and financial satisfaction, and influence of financial efficacy to financial satisfaction. Based on the result is found that three hypothesis are accepted. These means, there are difference between woman and man in financialefficacy and financial satisfaction. Other result that financial efficacy gave significant impact to financial satisfaction.